2017
DOI: 10.1007/s10661-017-6417-1
|View full text |Cite
|
Sign up to set email alerts
|

Indexing method for assessment of pollution potential of leachate from non-engineered landfill sites and its effect on ground water quality

Abstract: Dumping of solid waste in a non-engineered landfill site often leads to contamination of ground water due to leachate percolation into ground water. The present paper assesses the pollution potential of leachate generated from three non-engineered landfill sites located in the Tricity region (one each in cities of Chandigarh, Mohali and Panchkula) of Northern India and its possible effects of contamination of groundwater. Analysis of physico-chemical properties of leachate from all the three landfill sites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 40 publications
0
44
0
1
Order By: Relevance
“…Management of solid waste is a major challenge in several countries, especially in developing countries with high rate of population growth. In developing countries, mostly, solid wastes are dumped in engineered landfilled sites (Shaker and Yan, 2010) or nonengineered landfilled sites (Rana et al ., 2018; Sharma et al ., 2019). Landfills have been identified to have serious threat to the environment if not handled and operated appropriately (Talalaj and Biedka, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Management of solid waste is a major challenge in several countries, especially in developing countries with high rate of population growth. In developing countries, mostly, solid wastes are dumped in engineered landfilled sites (Shaker and Yan, 2010) or nonengineered landfilled sites (Rana et al ., 2018; Sharma et al ., 2019). Landfills have been identified to have serious threat to the environment if not handled and operated appropriately (Talalaj and Biedka, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of ground water to leachate is further increased by excess rainwater (Nagarajan et al ., 2012). Leachate may contain organics, inorganic salts and heavy metals within it (Mojiri et al ., 2014; Rana et al ., 2018). These leachate constituents are mainly a function of the age of the landfill and the degree of waste stabilisation (Talalaj and Biedka, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of leachate from a landfill site used since the 1990s using statistical tools confirmed the interaction between leachate and underground and surface waters, as demonstrated in several studies (Przydatek 2019a ; Przydatek and Kanownik 2019 ; Vahabian et al 2019 ). According to Rana et al ( 2018 ), an applied multidimensional statistical analysis is used in environmental monitoring or dataset modelling to reduce dimensionality and deviation, which is helpful in data evaluation.…”
Section: Discussionmentioning
confidence: 99%